Perancangan Perabot Penunjang Aktivitas Tunggu pada Ruang Tunggu ICU - Felycia Santoso; Grace Mulyono; Poppy Firtatwentyna Nilasari (Intra, 2018)
Based on our experience, indonesian in general tends to have a great emphaty when their loved one is ill and being treated in the hospital. This phenomenon especially occurs when the ailing family member is in critical condition and being treated in the ICU. The patients family tends to wait in the ICU waiting room throughout the duration of patients stay in the ICU. ICU waiting room is the main facility in the hospital to provide comfortable atmosphere for the patient’s family while waiting for their family member in the ICU. The comfort of the waiting room inherently connected to the availability of furnitures that will  satisfy its user needs. The furniture design for ICU waiting room aims to create furnitures that can provide comfort for the user’s various activities during their waiting period in the waiting room while conforms to the hospital standard of material and practice. The furniture design method used is the design thinking method with 10 steps, that is discovery, observe, empathize, leverage stories to discover insights, frame and reframe, ideate, decide, prototype, validate your idea, and iterate. Based on the methods above we produce 5 alternative designs which would have the same functionality for the various activities done in ICU waiting area in such as sitting and resting for long period of time while also providing storage space in high turnover condition. It is also hospital requirement for the furniture to use non-toxic, easy to clean material as to prevent bacterial spread. The existence of this design gives new ideas to improve patient’s family members comfort during their stay in the ICU waiting room.